The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1111/1365-2664.14020
|View full text |Cite
|
Sign up to set email alerts
|

Multispecies modelling reveals potential for habitat restoration to re‐establish boreal vertebrate community dynamics

Abstract: The restoration of habitats degraded by industrial disturbance is essential for achieving conservation objectives in disturbed landscapes. In boreal ecosystems, disturbances from seismic exploration lines and other linear features have adversely affected biodiversity, most notably leading to declines in threatened woodland caribou. Large‐scale restoration of disturbed habitats is needed, yet empirical assessments of restoration effectiveness on wildlife communities remain rare. We used 73 camera trap deploymen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 65 publications
1
12
0
Order By: Relevance
“…Idiosyncratic species responses to landscape disturbance are a common thread across taxa in monitoring studies from the OSR, and mammal monitoring work has demonstrated that consideration of a complexity of covariates may be required when assessing the impacts of landscape disturbance. For example, various levels of seismic line regeneration, snow cover, human use, line density, and line width can differentially alter the magnitude and direction of occupancy rates for different species (Tattersall et al, 2020a ), and the effect of these covariates likely changes at different temporal and spatial scales (Beirne et al, 2021 ; Tattersall et al, 2020b ). Consequently, while species‐level focused monitoring may be useful for indicator or focal species, this approach may be too resource‐intensive for widespread application.…”
Section: Resultsmentioning
confidence: 99%
“…Idiosyncratic species responses to landscape disturbance are a common thread across taxa in monitoring studies from the OSR, and mammal monitoring work has demonstrated that consideration of a complexity of covariates may be required when assessing the impacts of landscape disturbance. For example, various levels of seismic line regeneration, snow cover, human use, line density, and line width can differentially alter the magnitude and direction of occupancy rates for different species (Tattersall et al, 2020a ), and the effect of these covariates likely changes at different temporal and spatial scales (Beirne et al, 2021 ; Tattersall et al, 2020b ). Consequently, while species‐level focused monitoring may be useful for indicator or focal species, this approach may be too resource‐intensive for widespread application.…”
Section: Resultsmentioning
confidence: 99%
“…Sixty CT sites were on seismic lines and 13 were off of seismic lines. On‐line sites were further stratified by restoration category (treated, regenerating, unrestored control, human use; details in Beirne et al, 2021 ). In the Richardson study area, CTs were deployed in November 2017 and 2018 at 57 sites stratified by in (27) vs. out (30) of burned area and on (18) vs. off (39) of a seismic line, with year‐round sampling continuing until November 2019 (Burgar & Burton, 2019 ).…”
Section: Methodsmentioning
confidence: 99%
“…At each CT site, we quantified line of sight (LOS) as an indicator of habitat openness, under the assumption that ungulates would be less likely to use more open habitats with greater visibility, where the risk of predation may be higher (Dickie et al, 2020 ). Previous analysis showed that LOS was a useful descriptor of variation in linear feature conditions with respect to wildlife use in the Algar landscape (Beirne et al, 2021 ). We measured LOS (in m) along the seismic line or game trail perpendicular to the camera.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Camera-trap research spans the ecological hierarchy, with applications to animal behavior (Caravaggi et al, 2017(Caravaggi et al, , 2020 such as diel activity (Frey et al, 2017;Rowcliffe et al, 2014), populations (Bischof et al, 2020;Gardner et al, 2010), species' distributions (Rich et al, 2017;Tobler et al, 2015), and wildlife communities (Ahumada et al, 2011;Wittische et al, 2021). With adequate inferential logic and analysis, more complex ecological processes such as species interactions can also be discerned (Beirne et al, 2021;Clare et al, 2016;Niedballa et al, 2019). The field is rich for the planting seeds of new ideas.…”
mentioning
confidence: 99%